Impact of Strict and Lenient Heart Rate Control on Six-Minute Walk Test and Quality of Life in Atrial-Fibrillation Patients with Rheumatic Mitral Stenosis : Randomized Control Trial - Dwigustiningrum, Nur Kaputrin; Rizal, Ardian; Putri, Valerinna Yogibuana Swastika; Rahimah, Anna Fuji; Rohman, Mohammad Saifur; Wikananda, Adhika Prastya; Waranugraha, Yoga; Astiawati, Tri; Laitupa, Fitranti Suciati (Universitas Brawijaya, 2024)
Background: Recent studies showed no outcome difference between strict and lenient rate control in the general Atrial Fibrillation (AF) population. However, for AF and Rheumatic Mitral Stenosis (RMS) patients, evidences were lacking.Objective: To assess the impact of strict and lenient heart rate control on the Six-Minute Walk Test (SMWT) and Health Related Quality of Life (HRQoL) in patients with AF and RMS.Material and Methods: A prospective multicenter trial across tertiary hospitals in East Java assessed strict and lenient heart rate control's impact on the SMWT and HRQoL in AF and RMS patients. Sixty-one participants were randomized into strict and lenient groups over six months from March to August 2023. Medications were adjusted to achieve target heart rates, and HRQoL was assessed using SF-36 and SMWT at baseline and three months post-target heart rate attainment.Result: In our study, 29 patients were under strict heart rate control, and 32 were under lenient control. We found a decrease in HRQoL across all subscales, with significant differences observed in general health perception and physical function among those under strict control (p=0.002 and 0.03, respectively). However, no significant disparity was found in the SMWT distance difference between lenient and strict groups (p=0.529), nor in METs (p=0.326).Conclusion: In the study, lenient heart rate control demonstrates significant effects on the general health perception and physical function subscales compared to strict heart rate control.Â